Performance analysis of packed U-cell based inverter-fed five-phase induction motor drive using SINPWM technique - Ahmed Riyaz; Pradip Kumar Sadhu; Atif Iqbal; Md. Abdullah Ansari (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
Induction motor is the backbone of current industrial applications. Multiphase machines can handle high power application easily. With the use of five-phase induction motor, advantage of both multi-phase and induction motor can be achieved. This paper presents analysis of five-phase seven level-based Induction motor system fed by packed U-cell based inverter. Modelling of five-phase induction motor is done with the help of mathematical equations using d-q axis transformation. Inverter voltage output comes to be approximately sinusoidal with 18.07% Total Harmonic Distortion (THD). Induction motor with specified parameters is simulated under no-load condition and attains steady state conditions after transient state.